2021
DOI: 10.3390/nano11010145
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle and Bioparticle Deposition Kinetics: Quartz Microbalance Measurements

Abstract: Controlled deposition of nanoparticles and bioparticles is necessary for their separation and purification by chromatography, filtration, food emulsion and foam stabilization, etc. Compared to numerous experimental techniques used to quantify bioparticle deposition kinetics, the quartz crystal microbalance (QCM) method is advantageous because it enables real time measurements under different transport conditions with high precision. Because of its versatility and the deceptive simplicity of measurements, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 98 publications
0
12
0
Order By: Relevance
“…However, one should mention that the analysis of QCM measurements is a demanding task, because the oscillation frequency and the energy dissipation signals depend on the force exerted on the sensor rather than on the particle mass. 40 , 41 If one considers a rigid contact, the net force includes the inertia component proportional to the particle mass and the hydrodynamic component, which can play a significant role. This effect is generally explained as the hydrodynamic solvent coupling leading to apparent hydration of protein layers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, one should mention that the analysis of QCM measurements is a demanding task, because the oscillation frequency and the energy dissipation signals depend on the force exerted on the sensor rather than on the particle mass. 40 , 41 If one considers a rigid contact, the net force includes the inertia component proportional to the particle mass and the hydrodynamic component, which can play a significant role. This effect is generally explained as the hydrodynamic solvent coupling leading to apparent hydration of protein layers.…”
Section: Resultsmentioning
confidence: 99%
“…Vimentin adsorption kinetic measurements were performed applying the quartz crystal microbalance (QCM) technique according to the protocol previously applied for fibrinogen and HSA. , This method exhibits pronounced advantages making possible real time, in situ measurements of adsorption/desorption kinetics under various transport conditions (diffusion, flow). However, one should mention that the analysis of QCM measurements is a demanding task, because the oscillation frequency and the energy dissipation signals depend on the force exerted on the sensor rather than on the particle mass. , If one considers a rigid contact, the net force includes the inertia component proportional to the particle mass and the hydrodynamic component, which can play a significant role. This effect is generally explained as the hydrodynamic solvent coupling leading to apparent hydration of protein layers. ,, …”
Section: Resultsmentioning
confidence: 99%
“…In this respect, the quartz crystal microbalance (QCM) method exhibits pronounced advantages, enabling precise, in situ deposition/desorption kinetic measurements for the nano- and microparticles under flow conditions. 37 51 However, these investigations were almost exclusively focused on spherical particles.…”
Section: Introductionmentioning
confidence: 99%
“…16 It also has a potential value in clinical diagnostics and medicine, 17 hydrogels, 18 gene delivery nanocarriers, 19 and anticancer drug carriers. 20 Quartz crystal microbalance (QCM), a sensitive mass sensor, 21 has a wide range of applications in many fields. 22,23 In the 1980s, Bruckenstein et al reported that a QCM could work in the liquid phase, which provided a new idea for biomedical research.…”
Section: Introductionmentioning
confidence: 99%
“…Quartz crystal microbalance (QCM), a sensitive mass sensor, has a wide range of applications in many fields. , In the 1980s, Bruckenstein et al reported that a QCM could work in the liquid phase, which provided a new idea for biomedical research . By coating on the sensor, two of the most convincing parameters, the frequency shift (Δ f ) and motional resistance shift (Δ R ), can be obtained by a QCM.…”
Section: Introductionmentioning
confidence: 99%